Human Resource Management Practices in the Ghanaian Banking Sector - Hansen- Thompson, Rachel (2007)
Abstract The concept of Human Resource Management (HRM) and environmental influences dominates most management literature today however, focus has been on developed countries and Asia with little research done on Africa especially, Ghana. The study therefore aimed at providing insight into HRM practices found in Ghana using case studies of two banks; Ghana Commercial Bank and Barclays Bank of Ghana Limited. Evidence from the case studies illustrates that, organisations in Ghana do reflect the current economic situation in Ghana but does not limit their choice of practices.